2012
DOI: 10.1590/s1806-11172012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Uma introdução à teoria dos táquions

Abstract: A teoria da relatividade, proposta no início do século XX, aplica-se a partículas e referenciais que se movimentam com uma velocidade menor que a da luz. Nesse artigo mostraremos como esta teoria pode ser estendida a partículas e referenciais que se movimentam mais rapidamente que a luz. Palavras-chave: táquions, superluminal, relatividade, neutrinos, transformações de Lorentz estendidas, funções hiperbólicas estendidas, paradoxo de Tolman.The theory of relativity, which was proposed in the beginning of the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Finally, we want to highlight that although the gravitational interaction between two particles is always attractive, there is still an open question regarding the gravitational interaction between a particle and an antiparticle (some arguments defending that particles and antiparticles should repel each other are presented in [82,83]). We remark that although the concept of antiparticle is usually introduced in the scope of quantum mechanics, their existence can be evidenced as well from classical point of view, for instance, through the so-called Extended Theory of Relativity [84][85][86][87][88][89] − an extension of the special relativity theory that describes antiparticles and tachyons 9 . Let us present briefly the lines of reasoning that support the possibility of a gravitational repulsion between matter and antimatter.…”
Section: A Manifestly Covariant Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we want to highlight that although the gravitational interaction between two particles is always attractive, there is still an open question regarding the gravitational interaction between a particle and an antiparticle (some arguments defending that particles and antiparticles should repel each other are presented in [82,83]). We remark that although the concept of antiparticle is usually introduced in the scope of quantum mechanics, their existence can be evidenced as well from classical point of view, for instance, through the so-called Extended Theory of Relativity [84][85][86][87][88][89] − an extension of the special relativity theory that describes antiparticles and tachyons 9 . Let us present briefly the lines of reasoning that support the possibility of a gravitational repulsion between matter and antimatter.…”
Section: A Manifestly Covariant Approachmentioning
confidence: 99%
“…(133) A particle with negative energy that travels back in time should be, although, actually observed as an ordinary particle with positive energy, since any observer measures the time from the past to the future In this process of measurement, however, some properties of the particle must be reversed, in particular its electric charge -this is in fact the content of the Stueckelberg-Feynman principle. The reversion of the electric charge can be proved through the cpt theorem or in terms of the extended Lorentz transformations (from which the cpt theorem can be classically proved [86,88]). Now, the same argument that implies the reversal of the electric charge also must apply to the gravitational mass, since we had shown that both concepts are quite analogues.…”
Section: A Manifestly Covariant Approachmentioning
confidence: 99%
“…Transforms is well-known. The hyperbolic representation of generalized Lorentz transforms for superlight reference frames can be found in the papers [7,10]. At the same time, formula that would give a single hyperbolic representation for extended superluminal together with classical Lorentz transforms now is unknown.…”
Section: The Hyperbolic Representation Of Classical Lorentzmentioning
confidence: 99%
“…At the same time, formula that would give a single hyperbolic representation for extended superluminal together with classical Lorentz transforms now is unknown. In the paper [10] author tries to give such formula, using so-called extended hyperbolic functions. In the next section we construct the logarithmic extension of real number s 1 .…”
Section: The Hyperbolic Representation Of Classical Lorentzmentioning
confidence: 99%
See 1 more Smart Citation